Pengaruh Supervisi Akademik Pengawas Sekolah, Motivasi Kerja Guru, dan Sikap Profesional Guru Terhadap Kemampuan Guru Merencanakan Pembelajaran pada SMA Negeri Di Kabupaten Bantaeng - Nur Ahmad Rafiuddin Patta; Resky Pratiwi Hasmar (CV. Insight Publisher, 2023)
The research aimed to discover: (1) the influence of the implementation of academic supervision of school supervisors, teachers’ work motivation, and teachers’ professional attitude toward teachers’ ability in formulating lesson plan, (2) the influence of the implementation of academic supervision of school supervisors and teachers’ work motivation toward teachers’ ability in formulating lesson plan through teachers’ professional attitude in Public Senior High School in Bantaeng District. The research was survey with correlational design. The population of the research were all civil servant teachers in Public Senior High School in Bantaeng District. The samples were 103 teachers. The data collection techniques were questionnaire and test. Data analysis technique employed path analysis. The result of hypothesis test showed that: (1) the implementation of academic supervision of school supervisors, teachers’ work motivation, and teachers’ professional attitude had significant influence toward teachers’ ability in formulating lesson plan, (2) the implementation of academic supervision of school supervisors and teachers’ work motivation had more influence toward teachers’ ability in formulating lesson plan through teachers’ professional attitude in Public Senior High School in Bantaeng District.